2014
DOI: 10.1016/j.immuni.2014.08.006
|View full text |Cite|
|
Sign up to set email alerts
|

Human Dermal CD14 + Cells Are a Transient Population of Monocyte-Derived Macrophages

Abstract: SummaryDendritic cells (DCs), monocytes, and macrophages are leukocytes with critical roles in immunity and tolerance. The DC network is evolutionarily conserved; the homologs of human tissue CD141hiXCR1+CLEC9A+ DCs and CD1c+ DCs are murine CD103+ DCs and CD64−CD11b+ DCs. In addition, human tissues also contain CD14+ cells, currently designated as DCs, with an as-yet unknown murine counterpart. Here we have demonstrated that human dermal CD14+ cells are a tissue-resident population of monocyte-derived macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
267
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(294 citation statements)
references
References 53 publications
(75 reference statements)
27
267
0
Order By: Relevance
“…1f). These data extend recent observations that resident macrophages in some tissues express Zbtb46 19 , and showed that the amount of Zbtb46 expression, as inferred from the GFP reporter, discriminated between macrophages and cDC in the arterial wall. cDC were also distinguished from macrophages by expression of the integrin alpha X (CD11c) (Fig.…”
Section: Cd11bsupporting
confidence: 89%
“…1f). These data extend recent observations that resident macrophages in some tissues express Zbtb46 19 , and showed that the amount of Zbtb46 expression, as inferred from the GFP reporter, discriminated between macrophages and cDC in the arterial wall. cDC were also distinguished from macrophages by expression of the integrin alpha X (CD11c) (Fig.…”
Section: Cd11bsupporting
confidence: 89%
“…This would fit with our observations that CM numbers are elevated first, followed by IM. NCM numbers were not significantly elevated, which might be attributed to the longer NCM maturation time [20,21] . However, if the increased cell numbers observed in our study were caused by de novo production, monocyte maturation would have to be rapidly increased, as monocyte maturation appears to take 2 days (CM), 4 days (IM) or 7 days (NCM) under homeostatic conditions [20] .…”
Section: Differential Loss Of Monocyte Subsets From Circulation Aftermentioning
confidence: 85%
“…A labelling study in simian macaques [20] has shown that, under homeostatic conditions, CM are the first cells to be released from bone marrow, followed by IM and lastly by NCM. In humans, CM are the first cells to repopulate the bloodstream after hematopoietic stem cell transplantation [21] , making it likely that human monocytes follow a similar pattern. This would fit with our observations that CM numbers are elevated first, followed by IM.…”
Section: Differential Loss Of Monocyte Subsets From Circulation Aftermentioning
confidence: 99%
“…Indeed, it has been shown that LCs may originate from dermal CD14 + cells in noninflammatory settings in vitro (19). Other studies based on transcriptomic analyses have allowed reconsidering such CD14 + dermal cells as monocyte-derived macrophages most likely related to blood monocytes/macrophages rather than bona fide dermal DCs (20)(21)(22). However, whether these human monocyte-derived macrophages could differentiate into other cell types such as LCs in inflammatory conditions or at steady-state in vivo is still unclear.…”
mentioning
confidence: 99%